From the Warnock Report (1978) to an Education Framework Commission: A Novel Contemporary Approach to Educational Policy Making for Pupils With Special Educational Needs/Disabilities - Norwich, Brahm (Frontiers in Education, 2019)
This paper argues that the significance of the Warnock Report after 40 years goes beyond the impact of its deliberations and recommendations on UK policy and practice and its wider international influence. The Report’s significance also highlights the nature of provision for pupils with SEN and disabilities and the changing context of policy making in contemporary liberal democratic society. This paper shows the strong inter-connection between SEN and inclusion with other aspects of educational provision as the basis for proposing that future policy directions depend on general policy processes. It then argues that policy for pupils with SEN illustrates the democratic deficits in educational and policy-making processes in general. It uses this analysis to conclude that without grappling with these bigger policy issues we cannot expect some crucial questions in the field to be addressed more coherently and convincingly either conceptually or practically. Drawing on a post-democracy political analysis (Crouch, 2000). and contemporary ideas about deliberative democracy (Fishkin, 2018), with a recognition of the plural values that underlie policy tensions (Dahl, 1982). it proposes an Education Framework Commission (EFC). The Commission would set policy priorities as a settlement that has the potential to reconcile plural and sometimes contrary value positions. It would aim to design a ten-year consensual educational policy framework, within which political parties and governments will work; a framework that could be renewed after this period. An EFC would cover all key aspects of education including designs for including the diversity of learners. Finding common ground between different social and political value perspectives involves deliberative democratic principles and approaches that could influence representative democratic policy making. Though this proposal arises in an English context it has international relevance to the project of renewing ideas and values about the nature of schooling in a way that takes genuine account of SEN and disabilities.